Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan pada Kubik Koffie di Kota Padang - Mardona, Andre; Agus Sutarjo; Meri Dwi Anggraini (Ekasakti Matua Jurnal Manajemen, 2024)
This study aims to examine and analyze the effect of service quality and product quality on customer satisfaction at Koffie cubic in Padang city, where variable X is service quality and product quality. Dependent variable is customer satisfaction at Koffie cubic in Padang city. This study used a classical assumption test consisting of normality test, multiculity test, herosity test and multiple regression test, t test and F test. The results of the research on Service Quality Variables have a significant positive effect on Customer Satisfaction at Koffie Cubic in Padang City, variables have a positive and significant effect on Customer Satisfaction at Koffie Cubic in Padang City, that Service Quality and Product Quality simultaneously have a significant positive effect on Customer Satisfaction at Cubic Koffie in Padang City.